Vigicaen: A vigibase® Pharmacovigilance Database Toolbox. - Dolladille, Charles; Chrétien, Basile (The Journal of Open Source Software, 2025)
For decades, the World Health Organization (WHO) has been collecting adverse drug reaction reports, called Individual Case Safety Reports (ICSRs), from its member countries, populating more than 40 million reports to date.This pharmacovigilance database is called VigiBase® and is managed by the Uppsala Monitoring Centre in Sweden.(Uppsala Monitoring Centre, 2026) These ICSRs describe the course of patients who experienced an adverse event (a medical condition) after taking a drug.The burning question is whether this adverse event was actually related to the drug intake, e.g., if it is an adverse drug reaction (ADR).A pharmacovigilance database analysis aims at uncovering the very first potential signals of association between drugs and ADRs.(Montastruc et al., 2011) Disproportionality analysis, a method of safety signal detection, represents an essential component of pharmacovigilance.Advanced methodologies are essential when conducting disproportionality analyses, as traditional approaches are susceptible to various biases such as reporting bias and confounding.